Analisis Hasil Tanaman Perkebunan (Kopi Dan Teh) Menggunakan Regresi Linear - Hamidah, Isna (ESTIMASI: Journal of Statistics and Its Application, 2024)
Plantation crops are an agricultural sub-sector which also plays an important role in boosting the country's economy, one of which is coffee and tea. However, it is known from the Statistics Indonesia that data shows that the production of plantation crops has decreased, this is caused by one of the factors, namely due to the reduced area of plantation land caused by changes in the conversion of plantation land. The purpose of this study was to determine the influence of land area on the production of plantation crops with linear regression. The results of the study with linear regression analysis show that the variable area of land simultaneously or partially can affect the production of plantation crops, especially coffee and tea plant.